2011
DOI: 10.1039/c1cp22624j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ion–electron recombination in an expanding ultracold neutral plasma of NO+

Abstract: Using state-selected double-resonant excitation, we create a Rydberg gas of NO molecules excited to the principal quantum number n = 50 of the f-series converging to the ion rotational level, N(+) = 2. This gas evolves to form an ultracold plasma, which expands under the thermal pressure of its electrons, and dissipates by electron-ion recombination. Under conditions chosen for this experiment, the observed rates of expansion vary with selected plasma density. Electron temperatures derived from these expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 27 publications
8
29
0
Order By: Relevance
“…In a freely expanding plasma, the ambipolar pressure of the electron gas causes a radial acceleration of the ions [6]. The expansion we observe accords with this mechanism [19,20], and we find that the ions reach a terminal velocity that varies with the initial quantum number selected in the preparation of the Rydberg gas. Figure 1 plots terminal velocities of plasma expansion as a function of n 0 .…”
supporting
confidence: 74%
“…In a freely expanding plasma, the ambipolar pressure of the electron gas causes a radial acceleration of the ions [6]. The expansion we observe accords with this mechanism [19,20], and we find that the ions reach a terminal velocity that varies with the initial quantum number selected in the preparation of the Rydberg gas. Figure 1 plots terminal velocities of plasma expansion as a function of n 0 .…”
supporting
confidence: 74%
“…The plotted width begins to change slowly, then rises with a slope that reflects a ballistic radial ion velocity of 38 m s -1 . Previous work has shown that such a variation in width as a function of time for a simple laserproduced molecular beam plasma conforms reasonably with the Vlasov equations for a self-similar expansion of a quasineu tral Gaussian distribution of ions and electrons [11,16], much as observed in a MOT [1]:…”
Section: Discussionsupporting
confidence: 53%
“…Our model makes no provision for the dissociative recombination (DR) of NO+ with electrons [ 16,19], or for that matter, three-body recombination of ions and electrons, which can be expected to limit the density of shock structures in atomic as well as molecular plasmas.…”
Section: R(f) --= U(t) = Yi(t)n(t)mentioning
confidence: 99%
“…These plasmas are typically generated by photo-ionizing lasercooled gases [1] or gases in an ultrasonic jet [2]. They are diagnosed using three-body recombination [3][4][5][6][7][8], thermalization rates [9][10][11][12], electron evaporation or rf absorption [3,[13][14][15][16][17][18], charged particle imaging and detection [2,19], and optical fluorescence [12,20,21] and absorption [22][23][24]. Theoretical calculations and simulations [25][26][27][28][29][30][31][32] give great insights into the properties of these plasmas.…”
mentioning
confidence: 99%